Capsule robot for gut microbiota sampling using shape memory alloy spring. Issue 5 (14th August 2020) - Rehan, Muhammad; Al‐Bahadly, Ibrahim; Thomas, David G.; Avci, Ebubekir
Abstract: Background: Human gut microbiota can provide lifelong health information and even influence mood and behaviour. We currently lack the tools to obtain a microbial sample, directly from the small intestine, without contamination. Methods: Shape memory alloy springs are used in concentric configuration to develop an axial actuator. A novel design of sampling mechanism is fabricated for collecting the sample from the gut. Storage chamber (500 µl) is used to protect the sample from downstream contamination. Results: The developed actuator occupies a small space (5 × Ø5.75 mm) and produces sufficient output force (1.75 N) to operate the sampling mechanism. A non‐invasive capsule robot was tested ex vivo on the animal intestine, and it captured an average of 134 µl content which was sufficient for microbiome assessment. Conclusions: Laboratory testing revealed that the collected sample had an amino acid signature indicative of microbiota, mucus and digesta, which provided a proof of concept for the proposed design.